Effect of APOE‐E4 gene dose on regional early neuroinflammation and beta‐amyloid deposition in cognitively normal elderly volunteers: Neuroimaging / imaging and genetics. (7th December 2020) - Snellman, Anniina; Ekblad, Laura L.; Tuisku, Jouni; Helin, Semi; Bucci, Marco; Karjalainen, Tomi; Parkkola, Riitta; Karrasch, Mira; Rinne, Juha O.
Abstract: Background: Epsilon 4 allele (E4) of APOE gene is an important genetic risk factor for late onset Alzheimer's disease (AD). We investigated differences in regional neuroinflammation and beta‐amyloid (Aβ) deposition in vivo in cognitively normal homozygotic (Group 1: E4/E4) or heterozygotic (Group 2: E4/E3) carriers of the APOE*E4 allele in comparison to non‐carriers (Group 3: E3/E3), using [ 11 C]PK11195 and [ 11 C]PIB positron emission tomography (PET). Method: 60‐75‐year‐old participants with known APOE genotype were recruited via Auria Biobank (Turku, Finland). For this interim analysis, altogether 22 subjects with MMSE scores ≥ 26 were included (E4/E4 n=10; E4/E3 n=5; E3/E3 n=7). All participants underwent [ 11 C]PIB PET, [ 11 C]PK11195 PET, brain 3T‐MRI and neuropsychological testing. Tracer uptake was evaluated as standardized uptake value ratios (SUVR60‐90 ; [ 11 C]PIB) or distribution volume ratios (DVR; [ 11 C]PK11195) in a composite volume‐of‐interest (VOI) for Aβ deposition (including prefrontal cortex, precuneus, parietal cortex, anterior cingulate, posterior cingulate and lateral temporal cortex) and in medial temporal cortex for tau deposition. Analysis was performed using non‐parametric Kruskall‐Wallis and Spearman's correlation tests. Result: Differences between groups did not reach statistical significance yet in this interim analysis. However, a progressive increase in [11C]PIB uptake from E3/E3 (SUVR60‐90 1.8 ± 0.7) to E4/E3 (SUVR60‐90 2.0 ± 0.6) and E4/E4 (SUVR60‐90 2.4 ± 0.6) was already seen in the composite VOI including brain regions typical for early Aβ accumulation1 (Figure 1). CERAD total score had a fair negative correlation with [ 11 C]PIB composite SUVR60‐90 (rs = ‐0.48, p=0.023) in the whole population. In addition, a trend towards higher [ 11 C]PK11195 uptake in E4/E4 (DVR 1.26 ± 0.08) compared to E3/E3 (DVR 1.18 ± 0.03) in the composite VOI was detected (p=0.07), but no correlation between [ 11 C]PK11195 composite DVR and CERAD total score (rs = ‐0.13, p=0.58), or [ 11 C]PIB SUVR (rs= ‐0.005, p=0.98) was found. Conclusion: The study is still ongoing; however, the interim data suggest that cognitively intact elderly APOE*E4 carriers have both higher Aβ deposition and higher level of activated glia in the brain regions typical for early AD pathology.